Communication Between Dentists and Dental Technicians During the Fabrication of Removable Partial Dentures in Khartoum State, Sudan - SitAlgeel Arbab Ali; Nadia Khalifa; Mohammed Nasser Alhajj (University of Zagreb. School of Dental Medicine, 2018)
Objectives: To investigate the quality of communication between dentists and dental laboratory technicians in private dental laboratories in Khartoum State related to fabrication of removable partial dentures. Methods: This was a descriptive cross-sectional study, in which dental technicians were interviewed regarding the quality of instructions they received from dentists concerning the construction of removable partial dentures (RPD). Eighty cases were investigated, 69 acrylic (A-RPD) and 11 cobalt chromium (CC-RPD) dentures. Results: Although dentists provided no instructions in 21.7% of A-RPD cases, they gave instructions in all CC-RPD cases. Instructions were primarily given verbally (55.1% in A-RPD, 54.5% in CC-RPD cases), as opposed to written (23.3% in A-RPD, 45.5% in CCRPD cases). Most design components for A-RPD and CC-RPD cases were not clearly prescribed, and instructions were clear in only 8.7% of A-RPD and 36.4% of CC-RPD cases. Notably, surveying of casts by dentists was only done in 18.2% of CC-RPD cases. Most technicians (84.2%) believed that prosthesis design was the dentists' responsibility. Technicians needed to contact dentists for clarification of design significantly more frequently for CC-RPD (p=0.004) cases. Conclusion: Quality of communication between dentists and private laboratory technicians in Khartoum State with regard to removable partial denture construction was largely inadequate.